Effects of cypermethrin alone and in combination with leaf and seed extracts of neem against adult Tribolium castaneum (Herbst) - Khalequzzaman, M; Khanom, Makhsuda (University Journal of Zoology, Rajshahi University, 2007)
Cypermethrin was applied either alone or in combination with leaf and seed extracts of neem (Azadirachta indica A. Juss) to four strains of the adult red flour beetle Tribolium castaneum (Herbst) and the mortality was assessed after 24 and 48 hrs of treatments. The LD50 values were calculated as 0.0072, 0.0105, 0.0056 and 0.0124 μgcm-2 after 24 hours and 0.0041, 0.0076, 0.0046 and 0.0097 μgcm-2 after 48 hours of treatment for the Local, CR-1, FSS-II and CTC-12 strains respectively. The results showed synergism when applied in combined doses of cypermethrin and leaf and seed extracts with petroleum spirit, ethyl acetate and methanol. Leaf extract in acetone had an insignificant effect showing its inertness with cypermethrin excepting 24 hrs after treatment of Local strain and 48 hrs after treatment of CTC-12 strain. Seed extract in methanol in Local strain showed insignificant effect after 24 hrs of treatment but a synergistic effect occurred after 48 hrs of treatment.Key words: Cypermethrin, Azadirachta indica, Tribolium castaneum, synergismUniv. j. zool. Rajshahi Univ. Vol.25 2006 p.45-40